Evaluating the role and effectiveness of co‐produced community‐based mental health interventions that aim to reduce suicide among adults: A systematic review. (14th November 2022) - Hanlon, Claire A.; McIlroy, David; Poole, Helen; Chopra, Jennifer; Saini, Pooja
Abstract: Background: Suicide is a major public health risk requiring targeted suicide prevention interventions. The principles of co‐production are compatible with tailoring suicide prevention interventions to meet an individual's needs. Aims: This review aimed to evaluate the role and effectiveness of co‐produced community‐based suicide prevention interventions among adults. Methods: Four electronic databases (PsycInfo, CINAHL, MEDLINE and web of science) were systematically searched. A narrative synthesis was conducted. Results: From 590 papers identified through searches, 14 fulfilled the inclusion criteria. Most included studies elicited the views and perspectives of stakeholders in a process of co‐design/co‐creation of community‐based suicide prevention interventions. Conclusion: Stakeholder involvement in the creation of community‐based suicide prevention interventions may improve engagement and give voice to those experiencing suicidal crisis. However, there is limited evaluation extending beyond the design of these interventions. Further research is needed to evaluate the long‐term outcomes of co‐produced community‐based suicide prevention interventions. Patient and Public Involvement: This paper is a systematic review and did not directly involve patients and/or the public. However, the findings incorporate the views and perspectives of stakeholders as reported within the studies included in this review, and the findings may inform the future involvement of stakeholders in the design, development and delivery of community‐based suicide prevention interventions for adults.